Information Seeking Behaviour Patterns of Family Farmers and House-hold Food Security in Kisoga B Village, Ntenjeru Sub county in Mukono district, Uganda - Haumba, Eric Nelson; Kaddu, Sarah (University of Dar es Salaam Library Journal, 2021)
The paper examines how information seeking behaviour impacts on household food security of family farmers in Kisoga B village found in Mukono District in Uganda. Data were collected from 25 family farmers who were purposively selected from a total sample population of 178 residents in Kisoga B village. The study employed focus group discussions and unstructured interview method to gather quantitative data, which was analysed using descriptive statistics and thematic analysis respectively. Findings revealed that the major farming occupations practised by farmers in Kisoga B include: animal keeping, courtyard gardening and keeping of local fowls. Animals kept included cows, pigs, goats, sheep and rabbits. The study indicated that farmers need information on weather patterns, good agricultural practices, agricultural seeds and market information and farming technologies. Farmers confirmed that they get information from fellow farmers, neighbours, close friends who are not necessarily neighbours, burial places, over the radios/ televisions while others get information from marketplaces as they go vending. Findings also reveal that information sought by farmers enables them to do timely planting, access improved seeds for planting, improve on land management, pest and diseases control and management, improved storage of seeds and other produce, improve on food processing methods, identify current prices for farm inputs among other needs. The study concludes that information is a key resource for all agricultural activities regardless of their locations, social, economic and cultural status.